2014
DOI: 10.1159/000358001
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Needle Aspiration Cytology of Retroperitoneal Lesions: A 5-Year Experience with an Emphasis on Cytohistological Discrepancy

Abstract: Background: The retroperitoneal space contains various organs which can be affected by various non-neoplastic and neoplastic pathological processes. A diagnosis of these retroperitoneal lesions is often difficult. Fine-needle aspiration cytology (FNAC) under image guidance is now becoming an effective tool for the initial evaluation of retroperitoneal lesions. Objective: The present study was undertaken to evaluate the role of ultrasound-guided FNAC in the diagnosis of retroperitoneal lesions in comparison to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…The abstracts of the remaining 343 articles were reviewed, and the criteria for inclusion in the systematic analysis were determined. Twenty‐three articles 10–32 with a sample size >20 that presented data were included for which true‐positive and true‐negative rates could be calculated (comparing FNA vs. a follow‐up surgical pathology result as the gold‐standard method). The PRISMA flow chart is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The abstracts of the remaining 343 articles were reviewed, and the criteria for inclusion in the systematic analysis were determined. Twenty‐three articles 10–32 with a sample size >20 that presented data were included for which true‐positive and true‐negative rates could be calculated (comparing FNA vs. a follow‐up surgical pathology result as the gold‐standard method). The PRISMA flow chart is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Eight articles reported that rapid on‐site (cytologic) examination (ROSE) was performed during renal FNA. The data are summarized in Tables 2, 3, and 4 10–35 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite advances in diagnostic imaging techniques and the use of tumor markers, even with the development of spiral computed tomography (CT) and positron emission tomography (PET), the differentiation of pancreatic cancer and focal pancreatitis or other mass lesions, such as retroperitoneal or pelvic lesions remains problematic (1)(2)(3). Since the first report of endoscopic ultrasound (EUS)-fine needle aspiration (FNA) of the pancreas by Vilmann et al (4) in 1992, EUS-FNA has been considered as a standard method for the diagnosis of mass lesions in the pancreas because it is an effective and accurate procedure with a low complication rate (5)(6)(7)(8) and, moreover, it provides cytological or pathological confirmation of benign or malignant disease.…”
Section: Introductionmentioning
confidence: 99%